2022
DOI: 10.1371/journal.pntd.0010448
|View full text |Cite
|
Sign up to set email alerts
|

Molecular type distribution and fluconazole susceptibility of clinical Cryptococcus gattii isolates from South African laboratory-based surveillance, 2005–2013

Abstract: As is the case globally, Cryptococcus gattii is a less frequent cause of cryptococcosis than Cryptococcus neoformans in South Africa. We performed multilocus sequence typing (MLST) and fluconazole susceptibility testing of 146 isolates randomly selected from 750 South African patients with C. gattii disease identified through enhanced laboratory surveillance, 2005 to 2013. The dominant molecular type was VGIV (101/146, 70%), followed by VGI (40/146, 27%), VGII (3/146, 2%) and VGIII (2/146, 1%). Among the 146 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Previous studies in Western Africa have shown that strains already resistant to fluconazole or exhibiting an elevated fluconazole MIC were present in patients naïve for this molecule in Cameroon [ 31 , 32 , 33 ], Ivory Coast [ 34 ] and DRC [ 35 ]. From a general point of view, there is increasing FCZ resistance in Cryptococcus strains isolated from Africa [ 36 , 37 , 38 , 39 ]. Causes can be multiple, from continuous host exposure to fluconazole during the course of infection [ 40 ] to poor compliance with the treatments either for antifungals or HAART or faulty host defenses and location of infection [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in Western Africa have shown that strains already resistant to fluconazole or exhibiting an elevated fluconazole MIC were present in patients naïve for this molecule in Cameroon [ 31 , 32 , 33 ], Ivory Coast [ 34 ] and DRC [ 35 ]. From a general point of view, there is increasing FCZ resistance in Cryptococcus strains isolated from Africa [ 36 , 37 , 38 , 39 ]. Causes can be multiple, from continuous host exposure to fluconazole during the course of infection [ 40 ] to poor compliance with the treatments either for antifungals or HAART or faulty host defenses and location of infection [ 41 ].…”
Section: Introductionmentioning
confidence: 99%